Review of the Role of Political Economy with respect to Agricultural Policymaking in Africa - David, Mfote (International Journal of Scientific Research and Management (IJSRM), 2018)
The role of political economy in agriculture resurfaced with the 1980s economic reforms as development practitioners sought to roll back the state in supporting the sector. Despite development efforts by the international community to support agriculture, the sector continues to experience low growth, market and policy failures preventing it from significantly contributing to rural poverty eradication and foster widespread social development and economic growth. The research article reviews the role of politics in agricultural policymaking with emphasis on Sub Saharan Africa. The desk study reviewed secondary literature from pre and post-colonial period, from scholars in the field of political economy in the agriculture sector. The political economy of agricultural policymaking has significant impact on economic development and change in both developed and developing countries. Mixed development outcomes continue to be experienced especially in Sub Saharan Africa, and this calls for critical analysis of the political economy to have a clear understanding of the political and economic process. Future analysis should use scientific evidence to focus on the role of political leadership in Government and State Houses in agricultural policymaking comparing countries with similar characteristics